Investigation of electron cut-off in a cylindrical electrode system in pulsed magnetic field of an inductor - Drozd, I.; Kuzmichev, A.; Maikut, S.; Tsybulsky, L. (Вопросы атомной науки и техники, 2018)
The effect of electron cut-off from the anode in a cylindrical coaxial electrode system with an inhomogeneity of electric and magnetic fields along the axis is investigated by numerical simulation. The effect is caused by the pulsed magnetic field of the external inductor and the secondary magnetic fields generated by the eddy currents in the electrodes. The inhomogeneity of the fields is due to short length of the cathode and the inductor, and also by the internal protrusion at the anode opposite the cathode for the concentration of the magnetic field. The electrons escape along the axis from the interelectrode gap. To capture them, end cup-shaped collectors are introduced, for which the voltage of up to 300 V is applied when the anode voltage is of 10 kV. The results of the work can be used in designing a high-voltage current interrupter, for analyzing the conditions of magnetic initiation of a magnetron discharge, and the characteristics of magnetron electron guns.